Status and Development of Exotic Crops in Khandesh Region of Maharashtra (India): A Plea for Agrobiodiversity Conservation - Khairnar, S B; Patil, M V; Patil, D A (Plantae Scientia, 2021)
Selective utilization of limited crop species threatened some other crop species. This trend rendered some crop species into underutilised grain crops throughout. At this backdrop, the present authors inventorised agrobioversity in Khandesh region of Maharashtra(India). The area was visited in different seasons. The tribal farmers were interviewed to tap down information with respect to agroclimate, yield, characteristic features etc. Actual field visits were also made in study area. The crop species were deciphered using standard state, regional and district floras, besides the manuals and cyclopedia of cultivated plants. Total 17 exotic crop species were investigated belonging to cereals, millets, pulses and edible oil-yielders. The data accrued has been evaluated with the relevant national and international scenario. A need for their conservation is earmarked with particular emphasis on underutilised millets. The subject-matter is further dilated in view of their importance for the welfare tribal people in the area and developing countries.